Urinary organophosphate metabolites and oxidative stress in children living in agricultural and urban communities - Ratana Sapbamrer (2020)
© 2020, Springer-Verlag GmbH Germany, part of Springer Nature. Exposure to organophosphate (OP) pesticides in children may increase oxidative stress, resulting in the development of chronic diseases. This study aims to compare urinary OP metabolites and oxidative stress between children in agricultural and urban communities. The study also investigated the factors associated with urinary OP metabolites among children. Urine samples were collected from children for measuring levels of OP metabolites, glutathione (GSH), and malondialdehyde (MDA). The remarkable findings were that total dialkylphosphate (DAP) levels detected among children in this agricultural community were significantly higher than those from the urban community (P = 0.001). Multiple linear regression showed that total diethylphosphate (DEP) levels among children in the agricultural community were negatively associated with distances from children’s residence to the agricultural fields (β ± SE. = − 1.535 ± 0.334, 95%CI = − 2.202, − 0.863) and positively associated with playing on farms (β ± SE. = 0.720 ± 0.342, 95%CI = 0.036, 1.405). In addition, total dimethylphosphate (DMP) levels were positively associated with children working on farms (β ± SE. = 0.619 ± 0.264, 95%CI = 0.091, 1.147). Importantly, GSH levels among children in the agricultural community were significantly lower than those in the urban community (P < 0.001), but MDA levels did not differ. These results therefore suggest that children can be exposed to OPs both outdoors and indoors. Our results also provide supporting evidence that OP exposure can cause oxidative stress in children. As oxidative stress contributes to several chronic diseases, a good proposed strategy for the future would include measurement of oxidative stress biomarkers among children exposed to OPs as an early warning of chronic diseases.